New record of Parochlus carolinae (Chironomidae: Podonominae) from the Ventania hill system with the description of the female - Siri, Augusto (2014)
The first report of Parochlus Enderlein from Ventania hill system is presented, being the first record of the genus from Buenos Aires province. The description and illustration of the female adult of Parochlus carolinae Rodriguez et al. is presented and the original male and larval descriptions are emended. Characters from the pupal thoracic horn are emphasized to distinguish P. carolinae from other Parochlus species.